2019
DOI: 10.1002/uog.19021
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in vascular function parameters in pregnant women with chronic hypertension and association with adverse outcome: a cohort study

Abstract: There are persistent differences in vascular function parameters and brachial blood pressure through pregnancy in women with chronic hypertension who later develop adverse maternal and perinatal outcome. Further investigation of the possible clinical use of these findings is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Moreover, AS is significantly higher in women with HDPs compared to normotensive pregnancies and further increases with disease severity [52] . In recent studies, we and others have demonstrated that AS measurements can detect altered hemodynamic responses in the first trimester of pregnancy in women who subsequently develop HDPs [53] , [54] , [55] , [56] , [57] , [58] . PWA parameters, CO, and FMD are also outcomes of interest in our study as they provide complementary information regarding overall vascular function and have been reported to be associated with HDPs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AS is significantly higher in women with HDPs compared to normotensive pregnancies and further increases with disease severity [52] . In recent studies, we and others have demonstrated that AS measurements can detect altered hemodynamic responses in the first trimester of pregnancy in women who subsequently develop HDPs [53] , [54] , [55] , [56] , [57] , [58] . PWA parameters, CO, and FMD are also outcomes of interest in our study as they provide complementary information regarding overall vascular function and have been reported to be associated with HDPs.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, Webster L. et al performed a longitudinal assessment of BP and vascular function parameters in 97 pregestational hypertensive pregnancies. They demonstrated that those who subsequently developed superimposed PE and SGA, SBP and DBP were significantly higher from the first trimester to delivery (23).…”
Section: Discussionmentioning
confidence: 99%
“…A calibrated cuff-based blood pressure instrument, the arteriograph, will be used to obtain vascular readings, as recently used in a maternal hypertension trial [ 50 ]. Vascular health is included as a secondary outcome, as arterial function measures are more powerful than, and independent of, standard blood pressure for later prognosis [ 51 – 53 ].…”
Section: Interventionsmentioning
confidence: 99%